Simultaneous bilateral revision total knee arthroplasty following Abiotrophia defectiva infection. Issue 11 (3rd November 2020) - Wan, Joseph; Larsen, Matthew P; Panwalkar, Parag; Mofidi, Ali
Abstract : A 65-year old man presented with 6-week history of bilateral knee pain and swelling, with difficulty mobilising. He had bilateral total knee arthroplasties in situ performed 5 years prior complicated by postoperative wound infection. Bilateral synovial fluid cultures were positive for Abiotrophia defectiva, and extensive investigations had not identified an extra-articular source of infection. Failing debridement antibiotic and implant retention procedure, the patient underwent a simultaneous bilateral 2-stage revision with articulated cement spacers impregnated with vancomycin and gentamycin. The patient received 6 weeks of intravenous antibiotics after each stage. A. defectiva is a nutritiously fastidious organism, posing a challenge for clinical laboratories to isolate and perform antimicrobial susceptibility testing, yet prosthetic joint infections caused by A. defectiva are scarce in literature and present atypically with subacute signs of chronic infection. This poses a diagnostic and therapeutic challenge, and two-stage revision is the only documented treatment that successfully eradicates the infection.